Echinochloa crus-galli genome analysis provides insight into its adaptation and invasiveness as a weed. Issue 1 (December 2017) - Guo, Longbiao; Qiu, Jie; Ye, Chuyu; Jin, Gulei; Mao, Lingfeng; Zhang, Haiqiang; Yang, Xuefang; Peng, Qiong; Wang, Yingying; Jia, Lei; Lin, Zhangxiang; Li, Gengmi; et al.
Abstract Barnyardgrass (Echinochloa crus-galli ) is a pernicious weed in agricultural fields worldwide. The molecular mechanisms underlying its success in the absence of human intervention are presently unknown. Here we report a draft genome sequence of the hexaploid speciesE. crus-galli, i.e., a 1.27 Gb assembly representing 90.7% of the predicted genome size. An extremely large repertoire of genes encoding cytochrome P450 monooxygenases and glutathione S-transferases associated with detoxification are found. Two gene clusters involved in the biosynthesis of an allelochemical 2, 4-dihydroxy-7-methoxy-1, 4-benzoxazin-3-one (DIMBOA) and a phytoalexin momilactone A are found in theE. crus-galli genome, respectively. The allelochemical DIMBOA gene cluster is activated in response to co-cultivation with rice, while the phytoalexin momilactone A gene cluster specifically to infection by pathogenicPyricularia oryzae . Our results provide a new understanding of the molecular mechanisms underlying the extreme adaptation of the weed. Barnyardgrass is a problematic agricultural weed. Here, via genomic analysis, Guo et al. identify genes potentially underlying its success, including a gene cluster activated in response to co-cultivation with rice that leads to synthesis of the allelochemical DIMBOA.